Analysis Of Maladministration In The Online Licensing System In Indonesia - Aprianto, Sandi; Hermana, M. Arafat; Francisco, Dewa Jois (Fakultas Hukum Dehasen, 2025)
Digitization of licensing through an online licensing system aims to increase transparency and administrative efficiency. However, maladministration is still found, such as protracted delays, abuse of authority, and lack of transparency. This research uses a normative method with statutory and conceptual approaches. The research results show that technical obstacles, weak supervision, and personal interests are the main factors in maladministration. Recommended solutions include improving digital infrastructure, transparency of services, and strict sanctions for officials who abuse their authority. With these improvements, the online licensing system can run according to the principles of good governance.